Indomethacin treatment for patent ductus arteriosus in very low birthweight infants: double blind trial. Issue 4 (April 1983) - Rudd, P; Montanez, P; Hallidie-Smith, K; Silverman, M
Abstract : Thirty very low birthweight (VLBW) infants (mean gestational age 28.9 weeks; mean birthweight 1138 g) with symptomatic patent ductus arteriosus (PDA) were entered in a randomised double blind trial of indomethacin treatment. The mean age at diagnosis was 7.6 days and at entry to the trial 10.7 days. Before treatment for PDA the indomethacin and placebo groups were well matched for gestational age, birthweight, incidence of respiratory distress requiring mechanical ventilation, and fluid intake. Treatment was up to three daily doses of indomethacin 0.2 mg/kg or placebo by gastric tube and fluid restriction. During treatment there was a response in 13 out of 15 in the indomethacin group and in 3 out of 15 in the control group (P less than 0.001), but because of relapse the effect was maintained in only 7 out of 15 and 2 out of 15 respectively (P less than 0.05). No abnormalities were attributable to indomethacin, which is a safe and effective treatment for PDA in the VLBW infant, but the high relapse rate despite fluid restriction suggests that the best treatment has still to be found.